Level of Knowledge About Dental Health With Dental Caries - Vonny Amanda Rusmawaty; Bambang Hadi Sugito; Imam Sarwo Edi (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Dental and oral disease problems, especially dental caries, are common problems in Indonesia. Dental caries is a disease characterized by damage to hard tooth tissue on the surface of the teeth and spreads to deeper parts of the teeth. Including adolescents as a group that is vulnerable to dental and oral problems. The results of initial data collection showed a high percentage of dental caries (91%) in students of SMP Brawijaya Sakta 1 Surabaya. Limited knowledge about dental health can increase the risk of dental caries. To determine the relationship between the level of knowledge about dental health and dental caries in students of SMP I Brawijaya Sakta 1 Surabaya. For this study, the type of research used was analytical using the cross-sectional method. The number of research respondents was 39 students of SMP Brawijaya Sakta 1 Surabaya. The data collection instruments used were questionnaires to measure dental health knowledge and examination sheets to identify dental caries. The data analysis technique used the Chi Square Test. The test results from this study obtained an asymp.sig value (2-tailed) or a ρ value of 0.000 <α value (0.05). There is a significant relationship between the level of dental health knowledge and dental caries in students of Brawijaya Sakta 1 Middle School, Surabaya.